The Excavations at Khirbet el-Maqatir 1995-2001 and 2009-2016 : Volume 2: The Late Hellenistic, Early Roman, and Byzantine Periods - Hassler, Mark A.; Stripling, Scott (2023)
Khirbet el-Maqatir lies 16 km north of Jerusalem. The Associates for Biblical Research excavated 14 summer seasons and 5 winter seasons between 1995 and 2016. The remains range from Middle Bronze Age to Early Islamic and include a Bronze Age fortress, a Late Hellenistic/Early Roman village, and a Byzantine ecclesiastical complex. Volume 2 focuses on the later time periods.